Analysis of the Comparative Western Democracy, Pancasila Democracy, and the Concept of Shura; Study of the Book Manuscript "Democracy in Islamic Perspective by Ahmad Sukardja and Ahmad Sudirman Abbas" - Nurhasan Nurhasan; Siti Ngainnur Rohmah (JOURNAL of LEGAL RESEARCH, 2021)
Democracy that comes from the West is often juxtaposed with the concept of shura in Islam. The concept of shura is often seen as having an intersection with democracy. There are those who agree and there are those who are not in line with democracy. Those who agree with democracy argue that the value of democracy is universal and can coexist with Islam. The opinion that rejects an Islamic state (caliphate) and justifies democracy states that the legacy of the Islamic political system is based on the experience of the Caliphate with no standard standards. The author is interested and compelled to examine how Western Democracy, Pancasila Democracy, and the concept of Shura in an Islamic perspective? How do we compare the principles of western democracy, Pancasila Democracy and the concept of Shura in the book "Democracy in an Islamic perspective by Ahmad Sukardja and Ahmad Sudirman Abbas?" This study uses a qualitative research method, with a manuscript study approach. The results of this study state that Western Democracy and Pancasila Democracy in essence do not contradict the Shura principles, as long as the principles in them are in accordance with the essence of Islamic teachings. Western democracy is bound by equality of blood, race, language, and customs, whereas in Islam it does not see this bond as a barrier. Al-Qur'an and Al-Sunnah are more general in nature and cover all aspects of human life throughout the world. Meanwhile, Pancasila Democracy is only suitable for a country.Keyword: Western Democracy, Pancasila Democracy, Shura Concept, Islamic Perspective